The Principal Management in Improving Geography Teachers Performance at Public High School in Banda Aceh City - Nuranda, Puji; Murniati, Murniati; Bahrun, Bahrun (Jurnal Pendidikan Progresif, 2020)
The Principal Management in Improving Geography Teachers Performance at Public High School in Banda Aceh City. Objectives: The purpose of this research is to understand the program, implementation, evaluation, and obstacles faced by the principal in improving teachers’performance. Methods: This research was conducted by using descriptive method with qualitative approach. Data collection were conducted through interviews, observations, and documentation studies. The subjects of this research are principal, vice principal, head of subject teacher association, and geography teachers. The analysis data were conducted through data reduction, data display, draw a conclusion, and data verification. Findings: The results of this research shows (1) the planning of principal program was arranged at the beginning of school year by school development team and have been well documented. (2) the implementation of program started by giving instruction at the beginning of semester; (3) the evaluation was arranged at the end of semester and made as a follow up in determine the following program; and (4) the obstacles faced by principal in improving teachers’ performance is the lack of teachers understanding to attempts the improvement of teachers performance.Keyword: pincipal management, geography teacher, public high school.DOI: 10.23960/jpp.v10.i2.202007